Characterization of oxide scales formed on alloy 82 in nominal PWR primary water at 340 °C and in hydrogenated steam at 400 °C. (February 2018) - Duhamel, C.; Sennour, M.; Georgi, F.; Guerre, C.; Chaumun, E.; Crépin, J.; Héripré, E.; de Curières, I.
Highlights: Hydrogenated steam at 400 °C leads to the formation of a continuous Cr2 O3 surface layer. Only a spinel-type Ni(Fe, Cr)2 O4 oxide is formed in primary water at 340 °C. The formation of Cr2 O3 may be associated with a Cr-depleted layer in the substrate. A recrystallized layer with nanograins in the alloy leads to discrete oxide penetrations. High density of dislocations leads to a dense and random Cr-rich internal oxide network. Abstract: Alloy 82, used as weld metal in Pressurized Water Reactor (PWR), was exposed to hydrogenated steam at 400 °C and to simulated primary water at 340 °C. A comparative study of the oxide layer formed on the alloy surface in both environments was performed to confirm that steam conditions were representative of accelerated primary water conditions. For this purpose, the oxidation products were investigated at a nanometer scale using Scanning Electron Microscopy (SEM), X-ray Photoelectron Spectrometry (XPS) and Transmission Electron Microscopy (TEM). Results obtained in both conditions are compared and the influences of heat treatment, test duration and surface preparation are studied.